2009
DOI: 10.1108/01437720911004425
|View full text |Cite
|
Sign up to set email alerts
|

Internal wage dispersion and firm performance: white‐collar evidence

Abstract: Is internal wage dispersion good for firm productivity, or do internal wage differences break the conception of fairness and cause counterproductive behavior among workers? Contrary to previous empirical work that has found a positive relationship between internal wage dispersion and firm performance, this paper shows that such a relationship is not present using a unique linked employer-employee data set for white-collar workers in Norway over the period from 1986 to 1997. In the analysis, several different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…It is difficult to gauge if the findings reflect differential underlying patterns or whether multicollinearity issues played a role. Hunnes (2009) similarly decomposed pay dispersion into horizontal and vertical measures and tested for differential effects among a sample of more than 10,000 Norwegian organizations. He found that neither form of pay dispersion related significantly to a measure of organizational productivity.…”
Section: Organizational Performancementioning
confidence: 99%
“…It is difficult to gauge if the findings reflect differential underlying patterns or whether multicollinearity issues played a role. Hunnes (2009) similarly decomposed pay dispersion into horizontal and vertical measures and tested for differential effects among a sample of more than 10,000 Norwegian organizations. He found that neither form of pay dispersion related significantly to a measure of organizational productivity.…”
Section: Organizational Performancementioning
confidence: 99%
“…In contrast, they also found that horizontal dispersion would be negatively associated with the performance. Hunnes (2009) found pay dispersion did not show significant associations with organizational productivity.…”
Section: Theoretical Framework Payroll Dispersionmentioning
confidence: 79%
“…In other words, the status differences experienced by individual players in a team could prompt different perceptions of fairness regarding pay dispersion in the team, which may eventually influence individual or team performance. Hunnes (2009) insisted that horizontal disparity had a negative impact on organizational performance. According to Ding et al (2009) and Hunnes (2009), the practice of paying higher wages to more experienced and talented players through vertical pay dispersion could be a natural outcome that is beneficial in professional sports.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies on the relationship between WFWD and firm performance report diverging results. Some studies find a positive link (Iranzo, Schivardi and Tosetti, 2008;Lee, Lev and Yeo, 2008;Lallemand, Plasman and Rycx, 2009;Arranz-Aperte, 2014), others negative (Grund and Westergaard-Nielsen, 2008), yet other studies find a curvilinear relationship (Mahy, Rycx and Volral, 2011b) or non-robust, weak or no significant relationship at all (Hunnes, 2009;Liu, Tsou and Wang, 2010), and some find that the WFWD-performance link is moderated by firms' personnel policies and institutional environment (Jirjahn and Kraft, 2007;Mahy, Rycx and Volral, 2011a).…”
Section: Introductionmentioning
confidence: 99%